Sequential histopathology at the Rhipicephalus sanguineus tick feeding site on dogs and guinea pigs - Szabo, MPJ; Bechara, G. H. (Kluwer Academic Publ, 1999)
The tick Rhipicephalus sanguineus is a very common parasite of dogs worldwide. Dogs seem unable to acquire resistance against this tick species, whereas guinea pigs demonstrate a very strong resistance following primary infestation. We studied the inflammatory reaction at the R. sanguineus tick feeding site on dogs and guinea pigs during primary and tertiary infestations at different time intervals after attachment. Biopsies were collected after 4, 24, 48 and 96 hours. Changes that were found in all experimental groups included a cone of cement around the mouthparts of the tick, epidermal hyperplasia, edema and inflammatory cell infiltration in the dermis directly underneath the tick attachment site. Dogs reacted to ticks mainly with neutrophils, particularly after repeated exposure. Mast cells and mononuclear leukocytes were also present. Guinea pigs reacted to R. sanguineus mainly with mononuclear cells, eosinophils and basophils. These cells were particularly numerous after repeated exposure to R. sanguineus. Our results suggest that basophils and eosinophils are involved in resistance of guinea pigs to R. sanguineus and that neutrophils in dogs have little effect against this tick species.
Keywords: histopathology; leukocytes; dog; Guinea pig; resistance; tick; Rhipicephalus sanguineus